Assessing the Risk of Hospital-Acquired Clostridium Difficile Infection With Proton Pump Inhibitor Use: A Meta-Analysis. (28th September 2016) - Arriola, Vanessa; Tischendorf, Jessica; Musuuza, Jackson; Barker, Anna; Rozelle, Jeffrey W.; Safdar, Nasia
Abstract : BACKGROUND: Clostridium difficile is the principal infectious cause of antibiotic-associated diarrhea and accounts for 12% of hospital-acquired infections. Recent literature has shown an increased risk of C. difficile infection (CDI) with proton pump inhibitor (PPI) use. OBJECTIVE: To conduct a systematic assessment of the risk of hospital-acquired CDI following exposure to PPI. METHODS: We searched multiple databases for studies examining the relationship between PPI and hospital-acquired CDI. Pooled odds ratios were generated and assessment for heterogeneity performed. RESULTS: We found 23 observational studies involving 186, 033 cases that met eligibility criteria. Across studies, 10, 307 cases of hospital-acquired CDI were reported. Significant heterogeneity was present; therefore, a random effects model was used. The pooled odds ratio was 1.81 (95% CI, 1.52–2.14), favoring higher risk of CDI with PPI use. Significant heterogeneity was present, likely due to differences in assessment of exposure, study population, and definition of CDI. DISCUSSION: This meta-analysis suggests PPIs significantly increase the risk of hospital-acquired CDI. Given the significant health and economic burden of CDI and the risks of PPI, optimization of PPI use should be included in a multifaceted approach to CDI prevention. Infect Control Hosp Epidemiol 2016;1408–1417